Colocalising proteins and polysaccharides in plants for cell wall and trafficking studies - Lampugnani, Edwin R.; Persson, Staffan; van de Meene, Allison M. L. (Frontiers in Plant Science, 2024)
Plant cell walls (PCWs) are intricate structures with complex polysaccharides delivered by distinct trafficking routes. Unravelling the intricate trafficking pathways of polysaccharides and proteins involved in PCW biosynthesis is a crucial first step towards understanding the complexities of plant growth and development. This study investigated the feasibility of employing a multi-modal approach that combines transmission electron microscopy (TEM) with molecular-genetic tagging and antibody labelling techniques to differentiate these pathways at the nanoscale. The genetically encoded electron microscopy (EM) tag APEX2 was fused to Arabidopsis thaliana cellulose synthase 6 (AtCESA6) and Nicotiana alata ARABINAN DEFICIENT LIKE 1 (NaARADL1), and these were transiently expressed in Nicotiana benthamiana leaves. APEX2 localization was then combined with immunolabeling using pectin-specific antibodies (JIM5 and JIM7). Our results demonstrate distinct trafficking patterns for CESA6 and NaARADL, with CESA6 localized primarily to the plasma membrane and vesicles, while NaARADL1 was found in the trans-Golgi network and cytoplasmic vesicles. Pectin epitopes were observed near the plasma membrane, in Golgi-associated vesicles, and in secretory vesicle clusters (SVCs) with both APEX2 constructs. Notably, JIM7 labelling was found in vesicles adjacent to APEX2-AtCESA6 vesicles, suggesting potential co-trafficking. This integrative approach offers a powerful tool for elucidating the dynamic interactions between PCW components at the nanoscale level. The methodology presented here facilitates the precise mapping of protein and polysaccharide trafficking pathways, advancing our understanding of PCW biosynthesis and providing avenues for future research aimed at engineering plant cell walls for various applications.